Effect of 1, 4-bis(tert-butyl peroxy isopropyl) benzene on the rheological, mechanical, thermal and barrier properties of poly(butylene succinate-co-terephthalate)/poly(lactic acid) blends and blown films. (June 2022) - Yan, Xiangyu; Xie, Ruihong; Pan, Hongwei; Zhao, Tao; Han, Lijing; Bian, Junjia; Yang, Huili; Zhao, Yan; Wu, Guangfeng; Zhang, Huiliang
Abstract: In this article, 1, 4-bis(tert-butyl peroxy isopropyl) benzene (BIPB) was used as a reactive compatibilizer to enhance the compatibility between poly(butylene succinate-co-terephthalate) (PBST) and poly(lactic acid) (PLA) to prepare a novel environmentally friendly PBST/PLA-based blown film. Rheological analysis and gel permeation chromatography showed that BIPB reacted with PBST/PLA during melt-blending extrusion. The PBST/PLA blend gradually changed from the typical sea-island phase structure without BIPB towards a homogeneous phase structure with the increase in BIPB concentration, indicating that the compatibility between PBST and PLA improved significantly upon addition of BIPB. Moreover, compared to PBST/PLA blown film, the Young's modulus, tensile strength, breaking strain, tear strength, and falling dart impact strength of PBST/PLA/BIPB blown film showed great improvement. The PBST/PLA/BIPB blown film could control microenvironmental humidity in the packaging and inhibited mushroom molding and rotting for up to 7 days. In vitro cell experiments showed that the PBST/PLA/BIPB blown film was suitable for mouse fibroblast (L929) cell growth. Thus, the PBST/PLA/BIPB blown film can be used in fields such as biomedical materials, food packaging, and hygienic products. Graphical Abstract: ga1 Highlights: A novel PBST/PLA/1, 4-bis(tert-butyl peroxy isopropyl) benzene (BIPB) blown film was prepared. BIPB can improve the compatibility of PBST and PLA. PBST/PLA/BIPB blown films have better mechanical properties than PBST/PLA blown films. The PBST/PLA/BIPB blown film could inhibit mushroom molding and rotting for up to 7 days. The PBST/PLA/BIPB blown films were not cytotoxic to L929 cells and biocompatible.